Legal perspectives on state power : consent and control - Ashford, Chris; Reed, Alan (Matthew Alan); Wake, Nicola (Cambridge Scholars Publishing, 2016)
The issue of consent and criminal law commonly focuses on consent in sports, sexual activity, and medical treatment. The notion of consent and the influence of state control in this context, however, are pervasive throughout the criminal justice process from the pre-trial stage to rehabilitation. This edited collection charts an important and original pathway to understanding these important issues, pre-, during, and post-trial, from a range of perspectives, including doctrinal, socio-legal, intersectional, medico-legal, feminist, critical legal, and queer theoretical viewpoints. The collectio.